PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS PAPAN PINTAR PADA MATERI EKOSISTEM SISWA KELAS V SDI DHEREISA - Raga Moi, Maria Goreti; Kua, Maria Yuliana; Suparmi, Ni Wayan; Dinatha, Ngurah Mahendra (Dharmas Education Journal (DE_Journal), 2024)
New innovations that aim to improve the quality of student learning are based on existing problems in the school, it can be seen that students are not actively involved in the learning process because they use printed books as learning resources and use a sleepy lecture approach. One of the new innovations that will be made is smart board media. The purpose of this study is to create a smart board-based science learning media that focuses on ecosystem materials learned by grade V students at SDI Dheresia. The type of research used is Research and Development (R&D) development research. The development model is ADDIE, which has five stages: analyze, design, development, implementation, and evaluation. The smart board media developed is valid and suitable for use in learning. Data collection instruments include expert validation questionnaires and student and teacher response questionnaires. The validation of media experts was 90.4%, the validation of material experts was 89.8%, and the validation of linguists was 88.6%. The researcher conducted a product feasibility analysis to a limited group, consisting of eight grade V students and one teacher. The results of the product feasibility analysis response from eight students obtained a total score of 88% with very feasible criteria and the teacher's response results obtained a total score of 94.4% with very feasible criteria. Based on the results of the data collection instrument, it shows that the smart board-based science learning media is able to overcome the problems faced by students and teachers in the learning process.